Ubezpieczenie jako metoda finansowania ochrony zdrowia - Borda, Marta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Health insurance is considered to be one of the most popular methods of health care financing used in the contemporary health care systems. It allows to transfer sickness risk (an aspect of sickness risk resulting in medical expenses) from the individual to the group in return for paying the insurance premium. The paper deals with problems concerning health insurance used in the basic part of health care systems (usually obligatory health insurance) and in the form of voluntary health insurance products supplementing or improving (seldom substituting) the public health care services. It is important to underline the specific differences between these two kinds of health insurance, noticeable particularly in the method of distribution of the financial loss resulted from risk as well as in the calculation of the insurance premium and the way of its paying. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 56-64